Arabidopsis thaliana mTERF10 and mTERF11, but Not mTERF12, Are Involved in the Response to Salt Stress - Xu, Duorong; Leister, Dario; Kleine, Tatjana (Frontiers in Plant Science, 2017)
Plastid gene expression is crucial for plant development and acclimation to various environmental stress conditions. Members of the so-called “mitochondrial transcription termination factor” (mTERF) family, which are present in both metazoans and plants, are involved in organellar gene expression. Arabidopsis thaliana contains 35 mTERF proteins, of which mTERF10, mTERF11 and mTERF12 were previously assigned to the “chloroplast-associated” group. Here, we show that all three are localized to chloroplast nucleoids, which are associated with plastid gene expression. Knock-down of MTERF10, MTERF11 or MTERF12 has no overt phenotypic effect under normal growth conditions. However, in silico analysis of MTERF10, -11 and -12 expression levels points to a possible involvement of mTERF10 and mTERF11 in responses to abiotic stress. Exposing mutant lines for seven days to moderate heat (30°C) or light stress (400 µmol photons m-2s-1) fails to induce a phenotype in mterf mutant lines. However, growth on MS medium supplemented with NaCl reveals that overexpression of MTERF11 results in higher salt tolerance. Conversely, mterf10 mutants are hypersensitive to salt stress, while plants that modestly overexpress MTERF10 are markedly less susceptible. Furthermore, MTERF10 overexpression leads to enhanced germination and growth on MS medium supplemented with ABA. These findings point to an involvement of mTERF10 in salt tolerance, possibly through an ABA-mediated mechanism. Thus, characterization of an increasing number of plant mTERF proteins reveals their roles in the response, tolerance and acclimation to different abiotic stresses.